PENGELOLAAN HARTA PUSAKA TINGGI DI MINANGKABAU: Studi Kasus di Kubang Putiah Kecamatan Banuhampu Kabupaten Agam Sumatra Barat - Indrasukma, Andre (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2021)
A change in the management of pusaka tinggi (high heritage assets) in Nagari Kubang Putiah, Minangkabau, prompted this research. This article examines the position of pusaka tinggi in Nagari Kubang Putiah, as well as whether high inheritance management in Nagari Kubang Putiah is governed by Islamic law. The primary data came from interviews, while the secondary data came from literature studies on high heirlooms in Kubang Putiah. The findings show that, first, the position of high heirloom in Nagari Kubang Putiah is as a customary inheritance; second, the management of high heritage assets in Kubang Putiah has changed, not following the applicable provisions; and third, the management of high inheritance assets is following Islamic law, such as hibah (grants). Penelitian ini dilatarbelakangi oleh adanya suatu perubahan pengelolaan harta pusaka tinggi di Nagari Kubang Putiah, Minangkabau. Artikel ini menganalisis bagaimana kedudukan harta pusaka tinggi di Nagari Kubang Putiah, apakah pengelolaan harta pusaka tinggi di Nagari Kubang Putiah itu sesuai dengan Hukum Islam. Artikel ini merupakan hasil penelitian lapangan. Sumber data primer diperoleh dari wawancara, sedang data sekunder dari kajian literatur yang terkait dengan harta pusaka tinggi di Kubang Putiah. Hasil penelitian menunjukkan bahwa, pertama, kedudukan harta pusaka tinggi di Nagari Kubang Putiah adalah sebagai harta waris adat; kedua, pengelolaan harta pusaka tinggi di Kubang Putiah mengalami perubahan; ketiga, dari perspektif hukum Islam, pengelolaan harta pusaka tinggi dapat disamakan dengan harta hibah.